If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(6 + -1x) + 7x = 0 (6 * 4 + -1x * 4) + 7x = 0 (24 + -4x) + 7x = 0 Combine like terms: -4x + 7x = 3x 24 + 3x = 0 Solving 24 + 3x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-24' to each side of the equation. 24 + -24 + 3x = 0 + -24 Combine like terms: 24 + -24 = 0 0 + 3x = 0 + -24 3x = 0 + -24 Combine like terms: 0 + -24 = -24 3x = -24 Divide each side by '3'. x = -8 Simplifying x = -8
| z-3+4=-1 | | -9(-8x-4)-7=2x+29 | | 5x^2-20x+5=50 | | 37=-3+5(x+6) | | -5n-8(1+7n)=-8 | | x^2-12x+36=2x^2+23 | | 18x^2+3x= | | 117-6x=21x+18 | | 6-8x=150-36x | | 1x+25,5*5+2=50 | | 4x+5=-47-9x | | 5a=100 | | 3x-2(6-9x)=10x-45 | | 8x+6(-2x-7)=-41-5x | | (x-8)(5x+9)=0 | | -43-3x=7-9x | | (x+2)(x+2)=0.25 | | 3x^2y^4-81x^2y=x | | 10x-3=4x-5 | | 2*3x+3+3x+5=99 | | 2x+47=3x+14 | | 4x+8=89-56 | | x^2+4x+3.75=0 | | 8x^3-240x-9=0 | | 15x+60=0 | | 20x^2-45= | | 960/3= | | 24x^3+27x^2+7x+7= | | 24x^3+27x^2+7+7= | | 24x^3+27x^2+7x=7 | | x^2+x+0.25=0 | | 130-3x=24x-16 |